Revitalizing Health for All : Case Studies of the Struggle for Comprehensive Primary Health Care. - Labonté, Ronald (University of Toronto Press, 2017)
Revitalizing Health for All examines thirteen cases of efforts to implement CPHC reforms from around the globe including Australia, Brazil, Democratic Republic of Congo, Iran, South Africa, and more.